2010
DOI: 10.1128/jcm.02346-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vancomycin-Resistant Enterococcus faecium Isolated from Swine in Three Michigan Counties

Abstract: Vancomycin-resistant enterococci are a major cause of nosocomial infections but are rarely found in humans in the community and have not been identified in food animals in the United States. We evaluated a total of 360 fecal specimens from humans and their animals being raised for exhibit at three county fairs in Michigan. Fecal samples from 158 humans, 55 swine, 50 cattle, 25 horses, 57 sheep, 14 goats, and 1 llama were obtained and plated onto Enterococcosel agar containing 16 g/ml of vancomycin. Vancomycin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 60 publications
1
31
0
1
Order By: Relevance
“…The absence of glycopeptide resistance in swine enterococcal isolates in our study is likely because avoparcin or other related glycopeptide derivatives have never been used in the swine industry in the United States (12,34). However, isolation of vancomycin-resistant E. faecium (VRE) containing vanA has recently been reported from swine in Michigan (15). The source of VRE acquisition was not determined in the study, but there was no association between the occurrence of VRE and antibiotic administration in the pigs.…”
Section: Discussionmentioning
confidence: 87%
“…The absence of glycopeptide resistance in swine enterococcal isolates in our study is likely because avoparcin or other related glycopeptide derivatives have never been used in the swine industry in the United States (12,34). However, isolation of vancomycin-resistant E. faecium (VRE) containing vanA has recently been reported from swine in Michigan (15). The source of VRE acquisition was not determined in the study, but there was no association between the occurrence of VRE and antibiotic administration in the pigs.…”
Section: Discussionmentioning
confidence: 87%
“…They have frequently been isolated from farm animals, pets, and retail food products in Europe, but until very recently, the detection of VRE from either processing or production food animal environments in the United States was infrequent (11,20,42,53). There is limited evidence as to the direct role of the food chain in the dissemination of VRE among humans.…”
Section: Vre Isolates From Pigs (N ‫؍‬mentioning
confidence: 99%
“…The epidemiological background of the 41 isolates analyzed in this study is shown in Table 1. It includes representative isolates of VRE recovered from swine and healthy humans in national surveillance studies conducted in Portugal and Denmark (1995 to 2008) (references 17,26,35,37, and 38 and this study), strains widespread among swine from Switzerland and Spain (5,22), and the first VRE isolates recently recovered from animals in the United States (11). For comparison, we included a large and well-typed collection of clinical VRE isolates (140 E. faecium and 50 E. faecalis isolates) recovered from 23 countries, including Portugal, Spain, Denmark, and the United States, during the last 3 decades, most of which had caused hospital outbreaks (12,16).…”
Section: Methodsmentioning
confidence: 99%
“…However, situation changed the last years and vancomycin resistance was prevalent among 6 of 55 pig samples investigated in 2008 (Donabedian et al, 2010).…”
Section: Vancomycin Resistance Among Enterococci From Farm Animals Fmentioning
confidence: 99%